TECHNOLOGY FOR THE SEPARATION OF ANTHRACENE FROM THE SECONDARY PRODUCTS OF HYDROCARBON PYROLYSIS - Nurmanov Suvonqul Erhonovich; Ziyadullayev Anvar Egamberdiyevich; Ziyadullayev Anvar Egamberdiyevich; To'rayeva Dilrabo Fakhriddinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Introduction Hydrocarbon pyrolysis is a process of thermal decomposition of organic substances under high temperature conditions, resulting in the formation of valuable aromatic hydrocarbons. Among the secondary products released in this process are polycyclic aromatic hydrocarbons such as anthracene, phenanthrene, naphthalene, which are widely used in organic synthesis, pharmaceuticals and the production of dyes. Anthracene is mainly extracted from coal tar, but it is also found in certain quantities in oil and gas pyrolysis products. Improving the technology of anthracene extraction and its high purity extraction is one of the urgent problems of the industry. This work aims to develop a technology for extracting anthracene from the tarry fractions formed as a result of pyrolysis and to conduct its scientific and statistical analysis.